Indifferent but Mobilized: Rural Politics during the Interwar Period in Eastern and Western Europe. (3rd July 2018) - Brett, Daniel
ABSTRACT: What did peasants discuss at party meetings? Were they mobilized by ethnic politics or indifferent to them altogether? The end of the First World War brought about universal male suffrage in much of Europe, and with it the process of mass politics began. The concept of national indifference is important in understanding interwar politics, because this period is often studied teleologically with attention focused on extremism and nationalism as the primary mobilizing issue Agrarian movements have been under-researched, and when Agrarians have been studied, it has been through the prism of elite politics. This comparative paper seeks to redress this omission by looking at grassroots rural politics. The interwar countryside was marked by profound political, economic and social transformation but also in terms of what Robert Paxton has described as the 'triple crisis of the countryside' – worsening economic conditions, the declining status of the countryside and inadequate political representation. The paper will explore how reform and crisis impacted how agrarian politics functioned at a local level by asymmetrically comparing cases from Romania, Poland and Ireland, with the final case helping to contextualize Eastern Europe within the wider European experience This paper argues that the rural population was mobilized, but primarily in the context of local issues rather than national ethno-political questions. Local party organization was, to paraphrase James C Scott, the site 'of an exchange of small arms fire' in rural class conflict, as questions regarding the control of public space, generational conflict and power within the village mobilized peasants. Thus, I argue that it was the underlying socio-economic issues that mobilized the rural population, not nationalism. The dynamics of these conflicts were shaped by local economic, political and social power dynamics, and by using indifference as a concept, we can look more deeply at interwar politics from a grassroots perspective and develop a more nuanced understanding of local, national and European politics.